The housing stock, housing prices, and user costs: The roles of location, structure and unobserved quality - Jonathan Halket; Lars Nesheim; Florian Oswald (Centre for Microdata Methods and Practice (cemmap), 2015)
Using the English Housing Survey, we estimate a supply side selection model of the allocation of properties to the owner-occupied and rental sectors. We find that location, structure and unobserved quality are important for understanding housing prices, rents and selection. Structural characteristics and unobserved quality are important for selection. Location is not. Accounting for selection is important for estimates of rent-to-price ratios and can explain some puzzling correlations between rent-to-price ratios and homeownership rates. We interpret this as strong evidence in favor of contracting frictions in the rental market likely related to housing maintenance.
Keywords: 330